Portable water treatment plant project / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Construction of a conventional water treatment plant is costly and requires high maintenance; therefore, developing a portable and simple treated and water treatment for the community is crucial. The project aims to produce and provide an alternative portable treated water pond treatment plant, where the quality is as good as the conventional method. The project was led by Associate Professor Dr. Juferi Idris from the Chemical Engineering Department in UiTM Cawangan Sarawak. The pilot plant was built at a pond in UiTM Cawangan Sarawak, Samarahan campus. The treatment plant consists of a coagulation tank, mixing chamber, two clarifier tanks, aeration tank, sand filter, activated carbon and chlorination treatment and this ran for 24 hours continuously. The three main parameters were monitored for 7 days, measuring the water pH, turbidity, and Chemical Oxygen Demand (COD). The pilot plant was successfully carried out with less cost involved, easy to assemble and dismantle, making it a portable simple water treatment.